Determinants of Company Value With Information Transparency as Moderation In Food Beverage Sector Companies - Ristiyana, Rida; Atichasari, Anna Sofia; Abdullah, Rizki (Ilomata International Journal of Tax and Accounting, 2024)
This study aims to determine the effect of tax avoidance, company size, and leverage on company value with information transparency as moderation in food beverage sector companies listed on the IDX in 2017-2021. This type of research is quantitative research and the data used is secondary data. The population in this study amounted to 72 companies and obtained research samples using the purposive sampling method amounted to 13 companies. The data analysis method used is panel data regression analysis using Eviews version 10. The results simultaneously show that tax avoidance, company size and leverage affect company value. Partially, tax avoidance has a positive and significant effect on company value, while company size has a negative and significant effect on company value. Leverage and transparency of information do not affect company value. The results of the moderation effect prove that information transparency is not able to moderate the effect of tax avoidance on company value. On the other hand, information transparency is also unable to moderate the effect of leverage on company value. However, transparency of information can moderate by strengthening the influence of company size on company value.